(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To write an autobiography is an act of tremendous courage because in our society the habit of telling the truth is very less and the courage to listen and bear the truth is lesser than that. Dr. Tulsiram’s autobiography Murdahiya makes a special appearance in the list of those selected autobiography in which the truth of their experience is told by the author with enormous courage and without any hesitation. "Murdahiya" is a place where the dead bodies of humans and animals cremated which in Tulsiram’s word ’centre of Dalit existence’. This autobiography is an amalgamation of profound knowledge, thoughtfulness and spontaneity. Tulsiram gave a deep account of his personal experiences in Murdahiya.